Pneumococcal conjugate vaccines: a review of ethical considerations and socio-economic impact - Xu Han; Haiyang Yu; María Eugenia Toledo Romaní (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Pneumococcal conjugate vaccines (PCVs) have been available in many parts of the world for more than 15 years and are effective in preventing pneumococcal diseases in children. The WHO recommends the inclusion of PCVs in childhood immunization programmes worldwide. Objective: To value the approach to ethics and the socioeconomic impact of the conjugate pneumococcal vaccines. Material and Methods: A bibliographic review was carried out in databases such as PubMed and SciELO, considering reports from the WHO website. Development: It is globally considered that regulatory aspects, research results and informed consent (IC) of the subjects should be taken into account for the regulation, development and use of PCVs. In the context of countries such as China，the PCV13 of the Pfizer company is Class II due to its high import price.  In other contexts, such as Cuba, pneumococcal vaccination has not been introduced due to financial limitations. Research teams are working on the development of PCVs to reduce the cost of importing these vaccines, making the inclusion of PCVs in the national immunization program a reality. Despite the increasing complexity of vaccinology research, researchers will continue to be obliged to adhere to ethical principles. Conclusions: A cheaper pneumococcal conjugate vaccine would be needed to have a higher socioeconomic impact. Healthcare professionals have the obligation to be ethical and rigorous in vaccinology research. In addition, such research requires review by a national ethical review board and should be systematically monitored. It should be noted that studies in the pediatric population should be strongly regulated and controlled.